THE IMPORTANCE OF THE PẼMP RITUAL: FORMATION OF THE GAVIÃO INDIGENOUS SUBJECT IN THE MÃE MARIA INDIGENOUS LAND (Editora Impacto Científico, 2025)
This article aims to analyze the importance of the pẽmp ritual in shaping the indigenous subject of the Gavião people from the Mãe Maria Indigenous Land, located in southeastern Pará, Brazil. The pẽmp, traditionally performed with youth aged 12 to 20, is a rite of passage involving cultural, social, and spiritual practices, essential to the construction of both individual and collective identity. The research adopts a qualitative approach, based on bibliographic review, document analysis, and semi-structured interviews with indigenous leaders and elders who have experienced the ritual. The interviews were conducted between January and July 2024 and were key to understanding the formative impact of the pẽmp on youth. Additionally, the study draws from the lived experience of the author, an indigenous member of the community studied, which offers an internal and legitimate perspective. The results show that the pẽmp plays a central role in strengthening autonomy, cosmological bonds, collectivity, and respect for ancestral traditions. The discontinuity of this ritual may compromise the intergenerational transmission of knowledge crucial for the cultural survival of the Gavião people. Thus, the study reaffirms the relevance of the pẽmp as an educational and formative practice that resists external influences and strengthens ethnic identity in contemporary contexts.